INVESTIGAÇÃO DAS DIMENSÕES DA EDUCAÇÃO AMBIENTAL ABORDADAS PELOS LIVROS DIDÁTICOS DE CIÊNCIAS E BIOLOGIA E POR SEUS PROFESSORES - Fernandes, Regiane Matozo (2017)
The concern with natural resources, physical phenomena and human relationships guide Environmental Education (EA). In Brazil, EA is supported by law in all levels and modalities of education, such as the National Environmental Education Policy (PNEA), Law 9,795 of the year 1999. In 2012, the National Curricular Guidelines for Environmental Education (DCNEA), Which guide the educational perspectives of this theme in the school environment, both in print media, such as the Didactic Book (LD), and by the teacher. Research in EE points to problems faced by teachers for the implementation of EA from the textbook. Among these, it is highlighted the difficulty of teachers in recognizing the main approaches of EE. In this sense, the objectives of this research are to investigate how the environmental theme has been approached in textbooks and by the teacher, based on the trends of Critical EE, guided by the DCNEA; As well as to produce a pedagogical material that allows the identification of EA concepts present in school materials and practices as a way of facilitating reflective, critical and transversal teaching practice, according to the proposals presented in the DCNEA. Thus, this research presents the main public policies that guide EA in the school environment, as well as a reference of the main tendencies to approach this theme, as is the case of trends: conservative, pragmatic and critical. The methodological paths of this investigation began with the choice of the didactic book of Sciences and Biology, and elaboration of script for the interview with teachers. These research instruments were processed in order to obtain interpretations, according to the content analysis, proposed by Bardin (2004). The data presented are descriptive and qualitative. In this way it can be seen that in both LD and in the development of the subject by the teacher, there is coexistence of tendencies in the same content addressing the environmental theme. Regarding man's relation to nature, the conservative view prevails. The analysis is done at the individual level, while being biological, psychological and moral, the social construct is ignored. The causes of environmental problems, as well as the responsibilities of the crisis, are not critically discussed. For discussions involving social relations, social structure and collective struggle are not addressed, most of the time. Teachers have shown to be pragmatic in their attitudes towards the environment.